Mathematical modelling of advection-diffusion-reaction in ethanol production - Ahmad Izul Fakhruddin, Azimi (2024)
Ethanol produced through fermentation is one of the renewable energies that can be an alternative to conventional fossil fuel energy. However, high-volume ethanol production process is difficult to comprehend and expensive to operate. Therefore, in-depth research is required for optimal outcomes. Utilising a kinetic model is one of the most convenient method to experiment with the production of high-volume ethanol. However, the development of a practical kinetic model requires careful consideration of numerous factors. In addition, previous research has shown that the agitation parameters in the tank also have an impact on ethanol production. This study aimed to provide a solution strategy for modelling and simulation of agitation in the tank by extending and enhancing the kinetic model. In order to gain a deeper understanding of ethanol production, stability analysis of the non-dimensional model and parameter analysis were performed. In this system of mathematical equations, three stability points were found. In the meantime, the parameter analysis revealed only one parameter with positive effects and eight parameters that will hinder the ethanol fermentation process. This study additionally studied the impact of particle movement on the process of ethanol fermentation. The incorporation of particle movement components led to the formation of three separate systems of partial differential equations (PDEs), all of which were solved using the Finite Volume Method (FVM). The addition of particle movement elements to the model demonstrated a significant effect of advection-type movements on the ethanol production system. This study also determined the best value for advection to optimise production. The incorporation of fluid dynamics elements in the extended model of this study also allowed for the investigation of the ethanol production system’s agitator. The study found that the increase in the area of the free surface vortex from agitation and the increase in agitator speed reduce the volume of ethanol production. The analysis of the agitator’s position further revealed that agitation resulting in the production of a homogeneous solution increases ethanol production. The findings of this study can result in better estimations of ethanol production in agitated bioreactors and enhance understanding of particle behaviour in ethanol production system through fermentation.